Evaluación de cuatro tipos de sustratos orgánicos en la reproducción vegetativa de orquídeas cattleya en maceteros en el cantón Cayambe, Provincia de Pichincha - Godoy, Mario Eduardo (2013)
The present research took place in canton Cayambe, province of Pichincha. Cattleya orchids were treated with substrates made from organic matter. The treatments studied were the following: arable land, pumice, worm humus; arable land, pumice and sawdust; arable land, black land, pumice, rice husk; arable land, pumice and peat. Arable land was used as a witness. The complete randomly Block Design (BCA for its initials in Spanish) was applied with five treatments and three repetitions. The Tukey test was also applied at 5% for the comparison of the treatment measurements. The variables studied were the following: percentage of capture, the plant height, days before blooming, flower diameter, length of the flower bud, length of the flower stem, number of flowers by plant and the output of stems per hectare.